Sharia Principles In Risk Management In Islamic Banking: A Literature Review - Haikal, Mohammad; Efendi, Sumardi; Ramly, Arroyyan (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2024)
Islamic banking operates based on sharia principles, which strictly prohibit practices such as riba (interest), gharar (excessive uncertainty), and maysir (gambling). These prohibitions directly influence the approach to risk management. This study aims to review existing literature related to the application of sharia principles in risk management within Islamic banking. To thoroughly explore the topic, this study employed a library research method, which involved collecting, analyzing, and synthesizing information from various academic sources, including scholarly journals, books, and research reports.  The findings reveal that Sharia principles not only provide a unique framework for risk management but also strengthen the financial stability of Islamic banks by avoiding speculative practices and excessive uncertainty. Furthermore, the Sharia Supervisory Board (known as DPS) plays a crucial role in ensuring compliance with these principles. Thus, the application of Sharia principles in risk management significantly contributes to the sustainability and stability of Islamic banking. However, challenges remain, such as the limited availability of Sharia-compliant financial instruments. This study recommends further study to develop innovative and Sharia-compliant risk management instruments and strategies to support the future development of Islamic banking